A oralidade no texto teatral O abajur lilás , de Plínio Marcos - Fortanell, Gabriela Costa dos Santos (2014)
Nowadays, the spoken and written language are analyzed jointly and not dichotomously as once they were. Through recent studies, it is possible to infer that many features of these manifestations of language are shared. The occurrence of this phenomenon depends on the level of formality required, on the genre in which the speech is inserted, among other factors. Based on this perspective, this dissertation investigates how the marks of orality are presented in a theatrical text, in this case, in the play O Abajur Lilás, from the playwright Plinio Marcos, and what are the reasons that justify this use. For this research, we rely on the theory of Conversational Analysis and Sociolinguistics